Desenvolvimento profissional de universitários com deficiência: caminhos subjetivos e institucionais - Negrisoli, Letícia [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Professional development is one of the objectives of higher education, and students with disabilities face additional challenges in this process. This study aimed to develop and implement a professional development program for university students who self-identify as having a disability. This program aims to expand the possibilities for interventions and subjective, educational, and professional development for this population, as well as to equip higher education institutions to implement professional and career guidance services for students with disabilities. The research was qualitative and divided into two phases. The first phase used a questionnaire to characterize the participants, open-ended interviews, and the Career Development Scale for University Students (CDS), with qualitative data analysis. The second phase consisted of developing and implementing a professional development program, followed by analysis using the clusters of meaning methodology. The results indicated that the articulation between Historical-Cultural Psychology and Professional Guidance is a valuable tool in the professional development of individuals with disabilities. It was concluded that students with disabilities enrolled in higher education institutions could benefit from the implementation of professional and career guidance services, linking the university, the community and the job market, to promote the personal and professional development of these individuals throughout their lives.

A formação profissional é um dos objetivos do ensino superior, e estudantes com deficiência enfrentam desafios adicionais nesse processo. Este estudo objetivou a elaboração e aplicação de um programa de desenvolvimento profissional direcionado à universitários, autodeclarados como pessoa com deficiência a fim de ampliar as possibilidades de intervenções e desenvolvimento subjetivo, educacional e profissional para esta população bem como instrumentalizar instituições de ensino superior na implementação de serviços de Orientação Profissional e de Carreira para alunos com deficiência. A pesquisa foi qualitativa e dividida em duas fases. Na primeira fase, utilizou-se um questionário para caracterização dos participantes, entrevistas abertas e a Escala de Desenvolvimento de Carreira para Universitários (EDCU), com análise qualitativa dos dados. A segunda fase consistiu na elaboração e aplicação de um programa de desenvolvimento profissional, seguido de análise utilizando a metodologia de núcleos de significação. Os resultados indicaram que a articulação entre a Psicologia Histórico-Cultural e a Orientação Profissional é uma ferramenta valiosa no desenvolvimento profissional de indivíduos com deficiência. Concluiu-se que estudantes com deficiência matriculados em Instituições de ensino superior poderiam se beneficiar com a implementação de serviços de orientação profissional e de carreira, articulando a universidade, a comunidade e o mercado de trabalho, para promover o desenvolvimento pessoal e profissional desses indivíduos ao longo de suas vidas.
Professional development of university students with disabilities: subjective and institutional paths
Keywords: Pessoa com deficiência; Desenvolvimento profissional; Ensino superior; Orientação Profissional e de Carreira; Person with disability; Professional development; Higher education; Professional and counseling